DINAMIKA UPAYA MELAKUKAN SINERGI ANTARA HUKUM PERDAGANGAN INTERNASIONAL DAN HUKUM LINGKUNGAN - Endra Wijaya; Kikin Nopiandri; Habiburrokhman Habiburrokhman (Jurnal Hukum dan Peradilan, 2017)
In international trade activity, the law exists and becomes one of the important components to ensure the trading activity runs effectively, efficiently, and fair. Gradually, international trade system has started to embed environmental law issue to become its part of the system, and this process has begun since people realized that environment should be protected in order to support the sustainable development process. Currently, environmental law issue becomes an important condition for most of the international trade relations which are being done or will be done by subjects of the international trade. This paper focuses on how environmental law is being synergized within international trade system. The library research method will be used to explore that topic.Keywords: environmental law, international trade, international agreement